Antioxidant and antimicrobial activities of four medicinal plants from Algeria - Bellik, Yuva; Mekhoukh, Nasreddine (European Journal of Chemistry, 2023)
Medicinal plants are used in folk medicine to cure several human diseases. This work was designed to evaluate the antioxidant and antimicrobial activities of different extracts of Globularia alypum, Dittrichia viscosa, Juniperus oxycedrus, and Retama sphaerocarpa. The total phenolic content (TPC), the total flavonoid content (TFC), and the condensed tannin content (CTC) were determined spectrophotometrically. The antioxidant activity was tested using TAC, DPPH and reducing power assays. The agar diffusion method was used to determine antimicrobial activity against four bacteria (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa) and one fungus (Candida albicans). J. oxycedrus acetone extract showed the highest extraction yield (35.56±0.45%), TPC (504.96±14.82 mg GAE/g DE) and TFC (43.91±0.87 mg QE/g DE). The same extract exhibited the highest TAC (350.67±6.05 mg GAE/g DE) and was the most effective against the DPPH free radical (IC50 = 0.21±0.01 mg/mL). In contrast, the J. oxycedrus methanol extract showed the highest reducing power (A0.5 = 0.39 ± 0.09 mg/mL). All extracts tested showed antibacterial and anticandidal activities at different concentrations. The best antimicrobial effect was also observed with the acetone extract of J. oxycedrus against P. aeruginosa (26.77±0.06 mm), B. cereus (17.16±0.08 mm), E. coli (15.84±0.04 mm), and C. albicans (21.36±0.11 mm), while the ethanol extract of D. viscosa was the most active against S. aureus (24.54±0.03 mm). The results of this study provide a scientific basis for the traditional use of these local plants and demonstrate their potential as sources of natural antioxidant and antimicrobial bioactive compounds.